Effectiveness Of Using Village Funds In Improving Village Status Based On The Building Village Index (Idm) In Kuantan Singingi Regency - Andri Kurniawan; Rahyunir Rauf (UIR Press, 2021)
The Village Building Index in its application is used to map village development and independence based on the implementation of village laws. The index of developing villages is measured through three indicators, namely indicators of economic resilience, indicators of environmental resilience and indicators of social resilience. Identification of problems related to the effectiveness of using village funds based on the developing village index (IDM) in Kuantan Singingi Regency has not been effective, besides that the village government has obstacles in the use of village funds. The purpose of this study was to determine how effective the use of village funds was in improving village status based on the developing village index (IDM) in Kuantan Singingi Regency. Data collection techniques used in this study are through observation, interviews and documentation. Based on the results of the study, it shows that the effectiveness of using village funds in improving village status based on the developing village index (IDM) in Kuantan Singingi Regency is assessed according to the principle of using village funds according to village laws, namely to create villages with independent qualifications.